2019
DOI: 10.1002/ptr.6538
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the anti‐aging effects of phytoestrogens on collagen, water content, and oxidative stress

Abstract: Skin undergoes degenerative changes as it ages, which include the loss of elasticity, reductions in the epidermal thickness and collagen content, elastic fiber degeneration, and increased wrinkling and dryness. Skin aging can be significantly delayed by the administration of estrogen. Estrogen deficiency following menopause results in atrophic skin changes and the acceleration of skin aging. Estrogen administration has positive effects on human skin by delaying or preventing skin aging manifestations, but the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 98 publications
0
74
0
1
Order By: Relevance
“…These ndings suggested that the perinatal BPA exposure increased the levels of ARC-kisspeptin mRNA probably through antagonizing the E2 activity in ARC. It has been well-recognized that phytoestrogens could exhibit either estrogenic or anti-estrogenic effects depending on the endogenous estrogen levels and ER expression in different tissues [36].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings suggested that the perinatal BPA exposure increased the levels of ARC-kisspeptin mRNA probably through antagonizing the E2 activity in ARC. It has been well-recognized that phytoestrogens could exhibit either estrogenic or anti-estrogenic effects depending on the endogenous estrogen levels and ER expression in different tissues [36].…”
Section: Discussionmentioning
confidence: 99%
“…Phytoestrogens are a group of natural compounds, which have estrogen-like activity [160], with health benefits, such as a lowered risk of heart disease, breast and other hormone-dependent tumors, menopausal symptoms and osteoporosis. Three main categories of phytoestrogens, namely isoflavones, lignans and coumestans, are present in numerous vegetables (most notably soy), fruits and medicinal plants [161], and they are marketed as a natural alternative to estrogen replacement therapy.…”
Section: Estrogenic/antiestrogenic Activitymentioning
confidence: 99%
“…Their activities are due to the structural similarity with 17-β-estradiol, the primary female sex hormone that promotes the interaction with the two main α and β estrogen receptors. Consequently, phytoestrogens can act as agonists, partial agonists and antagonists [160,163]. Some isoflavones and flavones isolated from the aerial parts of Genista morisii and Genista ephedroides were in vitro evaluated for their estrogenic [164] and anti-estrogenic activities [165] by a yeast-based estrogen receptor assay.…”
Section: Estrogenic/antiestrogenic Activitymentioning
confidence: 99%
“…Isoflavones derived from soy beans have been widely used as potential anti-skin-aging compounds [ 5 , 6 ]. Numerous studies have reported that genistein, a major soy isoflavone, could suppress the generation of ROS and expression of MMP-1 and inducible nitrogen oxide synthase (iNOS), thereby exerting anti-wrinkle, skin-protective, and hydration effects against UV-induced photoaging [ 7 , 8 ]. However, due to its low skin permeability as well as low aqueous solubility, skin accumulation of genistein (NaCl solution; 140 mM) was only 0.1 μM per g of skin [ 9 ].…”
Section: Introductionmentioning
confidence: 99%